Bioceramic calcium phosphate-polymer scaffolds: A promising strategy for osteochondral repair and regenerative medicine - Li, Xiaohua; Noshadi, Bahareh; Motamedi, Kiana; Movahed, Emad; Behfarnia, Pouya; Semiroumi, D. T. (Elsevier Science Sa, 2023)
The study's objective was to fabricate a porous scaffold with desirable biological and bioactive characteristics, utilizing freeze-drying with polyvinyl alcohol (PVA). Subsequently, compressive strength tests and simulated body fluid (SBF) soaking experiments were performed to assess the mechanical and biological properties of the scaffold. X-ray diffraction (XRD) and scanning electron microscopy (SEM) were used for analyzing the scaffolds. The findings indicated that an increase in the amount of dicalcium phosphate decreased the porosity of the scaffold from 76% to 64%, raised the compressive strength from 2.48 MPa to 4.8 MPa, and lowered the dissolution rate from 39% to 24%. These changes led to an improvement in the scaffold's chemical bonding and stability. According to micromechanical models, the optimal scaffold composition was found to be 10 wt% of dicalcium phosphate in a polyvinyl alcohol mixture with constant drug content. Moreover, an increase in the dicalcium phosphate content led to an elevation in the drug release percentage due to the reduction in porosity and an increase in the drug release rate. The data were analyzed by using various kinetic models through diagrams generated by a UV device.
Keywords: Porous bony scaffold; Freeze-drying; Nanocomposite; Bioceramic; Osteochondral